2022
DOI: 10.48550/arxiv.2202.00651
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hydrodynamics and multiscale order in confluent epithelia

Abstract: We formulate a hydrodynamic theory of confluent epithelia: i.e. monolayers of epithelial cells adhering to each other without gaps. Taking advantage of recent progresses toward establishing a general hydrodynamic theory of p−atic liquid crystals, we demonstrate that collectively migrating epithelia feature both nematic (i.e. p = 2) and hexatic (i.e. p = 6) order, with the former being dominant at large and the latter at small length scales. Such a remarkable multiscale liquid crystal order leaves a distinct si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Our work paves the way for a deeper understanding of cell intercalation and other remodelling events in epithelial layers, where small-scale hexatic order (i.e. p = 6) has been recently discovered [64,65].…”
mentioning
confidence: 77%
“…Our work paves the way for a deeper understanding of cell intercalation and other remodelling events in epithelial layers, where small-scale hexatic order (i.e. p = 6) has been recently discovered [64,65].…”
mentioning
confidence: 77%
“…In this article, we explored the multiscale structure of in vitro layers of MDCK-II cells, with the goal of unveiling how the mechanical and biochemical properties of the monolayers and the substrate affect the crossover between hexatic and nematic orientational order. Such a remarkable example of multiscale organization in living matter has been recently identified by means of numerical simulations and experiments 30,31 , and has been conjectured to contribute to the biophysical versatility of epithelial tissues, whose tasks range from organism-wide morphogenetic migration to collective metastatic invasion under strong confinement. By comparing the behavior of two different cell lines -MDCK WT and the mesenchymallike MDCK E-cad KO cells -we showed that the existence of hexatic order crucially relies on E-cadherin-mediated intercellular adhesion, whose lack on MDCK E-cad KO cells rendered the cellular shape significantly elongated, hence prone to form nematic phases.…”
Section: Discussionmentioning
confidence: 99%
“…In this article, we explored the multiscale structure of in vitro layers of MDCK-II cells, with the goal of unveiling how the mechanical and biochemical properties of the monolayers and the substrate affect the crossover between hexatic and nematic orientational order. Such a remarkable example of multiscale organization in living matter has been recently identified by means of numerical simulations and experiments 30,31 , and has been conjectured to contribute to the biophysical versatility of epithelial tissues, whose tasks range from organism-wide morphogenetic migration to collective metastatic invasion under strong confinement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations